PENGARUH CAR, NPL, BOPO DAN LDR TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN - Heri Asmara, 07.05.52.0137; Poerwati, Tjahjaning (Students Journal of Accounting and Banking, 2012)
This study aims to determine the effect of CAR, NPL, BOPO, and LDRagainst the stock price.The sample in this study are listed banking companies on the Indonesia Stock Exchange in 2008-2010. Sampling technique using a purposive sampling technique (judge mental sampling) or sampling with certain criteria. Hypothesis testing is done using multiple linear regression.These results indicate that: CAR and NPL significant positive effect on stock prices, while BOPO and LDR have no significant positive effect on stock prices.Keywords: CAR, NPL, BOPO, LDR and Stock PriceÂ Â